Making gender integration more robust: Coaching livestock and fish projects on gender - Pyburn, Rhiannon (International Livestock Research Institute, 2016)
Interview with Rhiannon Pyburn (Royal Tropical Institute) for the book "A different kettle of fish? Gender integration in livestock and fish research": http://hdl.handle.net/10568/76684